Perancangan Website UMKM Neverland Shop Untuk Pengembangan Promosi Dan Pemasaran Produk - Dhiya Zalva; Nurul Izzah Azhari; Shofia Nabila (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
This research focuses on designing and developing a website for MSME Neverland Shop, a business engaged in toy creativity and innovation based in Padang City. The main objective of this project is to help Neverland Shop face the challenges of digitalization through the development of a responsive, attractive, and user-friendly website. The website is designed to expand market reach, increase online visibility, and improve operational efficiency through online ordering features and social media integration. This project also used a qualitative approach through interviews and observations to identify business needs and develop relevant digital solutions. The result of this research is a website that is expected to increase Neverland Shop's competitiveness in the wider market and have a positive impact on business development.